Comparison of rapid antigen testing and RT-PCR in the diagnosis of COVID-19 in Kashmir division - Magray, Tahir A.; Jabeen, Talat; Rather, Rouf H.; Nazir, Umar; Kumar, Muneer A.; Wani, Feroz A. (International Journal of Advances in Medicine, 2022)
Background: Accurate diagnosis and widespread use of diagnostic tests with easy access is important to contain the spread of SARS-CoV-2. A Real-time reverse transcription polymerase chain reaction (RT-PCR) has high cost and can be performed in special laboratories. There have been several easy to perform rapid antigen detection tests developed and recommended to use at point of care for timely detection of positive patients and their isolation to limit the spread of infection. The aim of the study was to compare the cost effectiveness and the role of RT-PCR and rapid antigen testing in diagnosing different suspects of COVID-19. Methods: In this cross-sectional study the data of all the suspected cases who underwent COVID-19 testing over a period of seven weeks at divisional level was used for analysis. Results: The widespread use of rapid antigen testing makes it more cost effective in detecting COVID-19 cases than the highly sensitive and specific RT-PCR testing. Conclusions: Rapid antigen tests can be used as a screening testing tool in high-risk groups to identify the infected persons quickly and for preventing the transmission of infection particularly in low resource settings.